Modelling periodontitis in vitro: engineering strategies and biofilm model development - Wang, Cong; Xu, Tian; Seneviratne, Chaminda Jayampath; Ong, Louis Jun Ye; Zhou, Yinghong (Frontiers in Biomaterials Science, 2024)
Periodontitis is a chronic inflammatory disease associated with dysbiosis in subgingival plaque biofilm, characterised by damage to the periodontal tissues, eventually leading to tooth loss. Hence, the pathophysiology of periodontitis and interaction between subgingival plaque and host tissue under various environmental cues are central to the pathogenesis of periodontitis. Therefore, engineering biofilm models that mimic in vivo pathophysiology is crucial to obtaining a clear insight into the pathology and developing targeted therapeutic methods. In this review, we provide a comprehensive overview of the engineering strategies employed of modelling oral biofilms focusing on surface attachment, fluid microenvironment, gas environment, shear force, microbial-host interaction and offer insights into the ongoing challenges and future perspectives, which will enable the development of novel physiological relevant models for oral biofilms.